Reducing antipsychotic drugs in stable patients with chronic schizophrenia or schizoaffective disorder: a randomized controlled pilot trial - Huhn, Maximilian; Leucht, Claudia; Rothe, Philipp; Dold, Markus; Heres, Stephan; Bornschein, Susanne; Schneider-Axmann, Thomas; Hasan, Alkomiet; Leucht, Stefan (European archives of psychiatry and clinical neuroscience, 2020)
As the course of schizophrenic disorders is often chronic, treatment guidelines recommend continuous maintenance treatment to prevent relapses, but antipsychotic drugs can cause many side effects. It, therefore, seems reasonable to try to reduce doses in stable phases of the illness or even try to stop medication. We conducted a 26 weeks, randomized, rater blind, feasibility study to examine individualized antipsychotic dose reduction versus continuous maintenance treatment (Register Number: NCT02307396). We included chronic, adult patients with schizophrenia or schizoaffective disorder, who were treated with any antipsychotic drug except clozapine, who had not been hospitalized in the last 3 years and who were in symptomatic remission at baseline. The primary outcome was relapse of positive symptoms. Symptom severity, social functioning and side effects were also examined as secondary outcomes. 20 patients were randomized. Relapse rates in the two groups were not significantly different. No patient had to be hospitalized. One patient in the control group dropped out. The mean reduction of antipsychotic dose in the individualized dose-reduction group was 42%, however only one patient discontinued drug completely. There were no significant differences in efficacy or safety outcomes. This randomized trial provides evidence, that reduction of antipsychotic medication in chronic stable schizophrenic patients may be feasible. The results need to be confirmed in a larger trial with a longer follow-up period.
CRIS-Team Scopus Importer:2020-02-28
Keywords: Antipsychotic maintenance treatment; Chronic schizophrenia; Dose reduction; Randomized clinical trial; Relapse